Determinan Ketahanan Pangan di Kabupaten Tulang Bawang Selama Pandemi Covid-19 - Della Krisna Prayuga (Departement of Mathematics Education, 2023)
Food security is one of the goals that must be maintained during the Covid-19 pandemic. However, the current economic conditions have caused a decrease in people's income due to a decrease in productive business activities, resulting in an increase in unemployment and poverty. This is quite worrying for the government in the event of a food crisis in the future. Tulang Bawang Regency is one of the regions that has felt the impact of the Covid-19 pandemic. Therefore, this study aims to determine the picture of food security in Tulang Bawang Regency and the variables that affect it. The results of the multinomial logistic regression analysis found that the small number of household members, high education of the head of the household, and the condition of poverty were not poor would increase the chances of these households to be food secure.